2018
DOI: 10.48550/arxiv.1811.12659
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulsating stars in binary systems: a review

Simon J. Murphy

Abstract: Binary systems anchor many of the fundamental relations relied upon in asteroseismology. Masses and radii are rarely constrained better than when measured via orbital dynamics and eclipse depths. Pulsating binaries have much to o er. They are clocks, moving in space, that encode orbital motion in the Doppler-shifted pulsation frequencies. They o er twice the opportunity to obtain an asteroseismic age, which is then applicable to both stars. They enable comparative asteroseismology -the study of two stars by th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 107 publications
(137 reference statements)
0
12
0
Order By: Relevance
“…These constraints are very useful for asteroseismical studies of pulsating stars in binaries. Various types of pulsating stars are known as members of binary systems (see the review by Murphy 2018). We placed V404 Lyr (KIC 3228863, Gaia DR2 2051369705923204224) on our spectroscopic observation program for eclipsing binaries (EBs) in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…These constraints are very useful for asteroseismical studies of pulsating stars in binaries. Various types of pulsating stars are known as members of binary systems (see the review by Murphy 2018). We placed V404 Lyr (KIC 3228863, Gaia DR2 2051369705923204224) on our spectroscopic observation program for eclipsing binaries (EBs) in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Given that B stars are known to have a high rate of multiplicity (Abt et al 1990;Sana et al 2013;Moe & Di Stefano 2017), it is noteworthy that we find so few in binary systems here. This is presumably due to the fact that B-type stars, like most classes of variable star, are not well-suited to a phase modulation analysis (Murphy 2018). Generally, high-frequency oscillators are more useful clocks, but the B stars that do oscillate at high frequencies -the sdB stars and white dwarfs -often show intrinsic phase modulation that make them poor clocks (Østensen et al 2014;Silvotti et al 2018;Zong et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Faster clocks (shorter-period pulsations) and more stable clocks allow the orbit to be determined more precisely. So far, the class of intermediate-mass stars on the main sequence known as δ Scuti stars has proved the most valuable for pulsationtiming studies (Compton et al 2016;Murphy 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A few months later, Kahraman Aliçavuş et al ( 2017) almost doubled the threshold of P orb by taking into account only the eclipsing systems. Murphy (2018) published a review for binaries with pulsating components including also those with δ Scuti members. Qian et al (2018), using the LAMOST spectra of more than 760 δ Scuti stars, found that 88 of them are possibly members of binary or multiple systems.…”
Section: Introductionmentioning
confidence: 99%